Combination of Endogenous Estradiol and Adipokine Leptin in Breast Cancer Risk and Prognosis Assessment in Postmenopausal Chinese Women - Luo, Yang; Li, Han-Bing; Zhang, Yue; Wu, Yu-Xin; Shen, Di; Che, Yi-Qun (Frontiers in Endocrinology, 2021)
Abstract Objective: Our study aims to clarify the role of estradiol and leptin in breast cancer risk and prognostic assessment in postmenopausal Chinese women. Design: The serum circulating estradiol and leptin level was detected by ELISA. Then the correlation between estradiol, leptin level and clinical characteristics was analyzed using the Fisher's exact test. Next, the Kaplan-Meier model was conducted to analyze the association between estradiol, leptin and prognosis of postmenopausal breast cancer patients in our cohort and TCGA dataset. Setting: The study was conducted at National Cancer Center, Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College. Patients: A total of 182 postmenopausal breast cancer patients and 111 healthy subjects from December 2010 to January 2017 were included in analysis. Another 702 cases with breast cancer were retrieved from The Cancer Genome Atlas (TCGA) database for subsequent analysis. Main outcome measure: Serum circulating estradiol and leptin level. Results: The level of estradiol was significant higher (P＜0.001) but the level of leptin had no significant difference (P = 0.764) in postmenopausal breast cancer patients compared with healthy subjects. The level of estradiol and leptin was not significantly different between estrogen receptor (ER) positive and ER negative groups (P＞0.05). Estradiol was significantly correlated with tumor T stage (P = 0.002) and leptin was significantly associated with perineural invasion (P = 0.014). In addition, the disease-free survival of patients with high level of estradiol was significantly shorter (P = 0.025) but leptin tended to be a protective factor for overall survival in TCGA analysis (P = 0.038). Conclusion: Circulating estradiol and leptin played important roles in the risk of postmenopausal breast cancer even in low-estrogen nations with independent expression of ER status. High circulating estradiol was a poor prognostic factor and leptin may be a protection signal in Chinese postmenopausal patients with breast cancer.